PERSEPSI PEMAKAI LAPORAN KEUANGAN TERHADAP INDEPENDENSI AUDITOR BPK DI KOTA PALU - Sukri, Fadil (Katalogis, 2017)
The aim of the research is to find out the difference of perceptions among financial statement users that include the government working units, legislative representative, and academics, Sample consists of 35 people consisting of 22 heads of the government working units, 8 legislatives, and 5 academics. Research method is descriptive qualitative and quantitative. Data of analysis uses Anova One-Way to test several indicators such as: 1) the length of audit, 2) the independence of the audit fees, 3) the limited time of the assignment of auditors, 4) kinship, 5) the tendency to straddle because of political beliefs or social, 6) the access to information without barriers, and 7) the freedom of determining the contents of the report, timeÂ  reporting, as well as publishing and disseminating the report. The result concludes that 1) different perceptions exist in three groups of financial users, 2) of 7 indicators, there is one factor that shows different perception towards auditor independency that is â€˜the limited time of the assignment of the auditor.